Isolation and assessment of gut bacteria from the Formosan subterranean termite, Coptotermes formosanus (Isoptera: Rhinotermitidae), for paratransgenesis research and application. (19th January 2016) - Tikhe, Chinmay V.; Sethi, Amit; Delatte, Jennifer; Husseneder, Claudia
Abstract: Paratransgenesis targeting the gut protozoa is being developed as an alternative method for the control of the Formosan subterranean termite (FST). This method involves killing the cellulose‐digesting gut protozoa using a previously developed antiprotozoal peptide consisting of a target specific ligand coupled to an antimicrobial peptide (Hecate). In the future, we intend to genetically engineer termite gut bacteria as "Trojan Horses" to express and spread ligand‐Hecate in the termite colony. The aim of this study was to assess the usefulness of bacteria strains isolated from the gut of FST as "Trojan Horses." We isolated 135 bacteria from the guts of workers from 3 termite colonies. Sequencing of the 16S rRNA gene identified 20 species. We tested 5 bacteria species that were previously described as part of the termite gut community for their tolerance against Hecate and ligand‐Hecate. Results showed that the minimum concentration required to inhibit bacteria growth was always higher than the concentration required to kill the gut protozoa. Out of the 5 bacteria tested, we engineered Trabulsiella odontotermitis, a termite specific bacterium, to express green fluorescent protein as a proof of concept that the bacteria can be engineered to express foreign proteins. Engineered T. odontotermitis was fed to FST to study if the bacteria are ingested. This feeding experiment confirmed that engineered T. odontotermitis is ingested by termites and can survive in the gut for at least 48 h. Here we report that T. odontotermitis is a suitable delivery and expression system for paratransgenesis in a termite species.